Crop-based irrigation operations in the North West Frontier Province of Pakistan. Vol.III: data collection procedures and data sets. Final report - Afaq, R.M.; Strosser, P.; Rehman, S.U.; Hakim, A.H.; Garcés-Restrepo, C. (International Irrigation Management Institute, 1994)
Final report of the Technical Assistance Study TA-1481 PAK